Prior learning assessment and recognition: Emergence of a Canadian community of scholars - Christine Wihak (Athabasca University Press, 2011)
Prior learning assessment and recognition (PLAR) is the practice of reviewing, evaluating, and acknowledging the information, skills, and understanding that adult learners have gained through experiential or self-directed (informal) learning rather than through formal education (Thomas, 2000). As our current economy and workplaces experience rapid and continuing change, PLAR offers a vital contribution to supporting lifelong and life-wide learning (Evans, 2000). Beyond significant benefits to individual adult learners in terms of confidence-building and enhanced reflective capacity, PLAR’s process translates personal and workplace learning into a portable format, a common coin suitable for public recognition in many different venues. PLAR has hence become an integral feature of lifelong learning policies around the globe and is closely linked with the implementation of national and transnational qualification frameworks (Morrissey et al., 2008).